Density functional theory (B3LYP and CAM-B3LYP) study on the electronic spectral properties of selected polyyne metabolities - Julian Andrei D. Monteclaro. 4 0 16; 5 (2022)
u
Thesis (Bachelor of Science in Chemistry) - Pamantasan ng Lungsod ng Maynila, 2022.
Keywords: 2 -- 0; 6; 20; 20; 2